Novel Predictor of the AF Development in Patients with OSAS: Importance of Visceral Adipose Index - Ugur OZKAN; Muhammet GURDOGAN (Medeniyet Medical Journal)
Objective: Obstructive sleep apnea syndrome (OSAS) is a sleep disorder whose frequency is increasing daily due to modern lifestyle. Patients with atrial fibrillation (AF), which has the same predisposing factors, frequently visit the outpatient clinic with complaints of palpitation. Existing symptoms are often associated with the course of OSAS, and the development of AF, a disease with high morbidity and mortality, cannot be detected. In our study, we investigated the relationship between the visceral adiposity index (VAI) and AF development in these patients. Methods: We retrospectively analyzed 207 patients with OSAS who visited the cardiology outpatient clinic. The data of 44 patients with AF and 163 patients without AF were compared. Results: Demographic characteristics and clinical risk factors were similar between the groups (p>0.05). VAI, apnea-hypopnea index, and inflammatory markers were higher in the AF group, and these risk factors were significant in the multivariate analysis (p<0.05). Conclusions: Our study is important in terms of showing VAI as one of the most important predictors of AF, which has an impact on mortality and morbidity in patients with OSAS, whose frequency is increasing daily. Further prospective studies are required to confirm our observations and determine their clinical applicability.